Multiple Cross Displacement Amplification Coupled With Gold Nanoparticles-Based Lateral Flow Biosensor for Detection of the Mobilized Colistin Resistance Gene mcr-1 - Gong, Lin; Liu, Ernan; Che, Jie; Li, Juan; Liu, Xiaoli; Xu, Huiqiong; Liang, Jiansheng (Frontiers in Cellular and Infection Microbiology, 2019)
Fast dissemination of the mobilized colistin resistance (mcr) gene mcr-1 in Enterobacteriaceae causes a huge threat to the treatment of severe infection. In the current report, a multiple cross displacement amplification (MCDA) coupled with the detection of amplified products by gold nanoparticles-based lateral flow biosensor (LFB) assay (MCDA-LFB) was established to identify the mcr-1 gene with simpleness, rapidity, specificity and sensitivity. The MCDA-LFB assay was performed at a isothermal temperature (63°C) for only 30 min during the amplification stage, and the reaction products were directly identified by using LFB which obtained the result within 2 min. The entire process of experiments, from templates extraction to result judging, was accomplished in less than 60 min. For the analytical specificity of this method, all of the 16 mcr-1-producing strains were positive, and all of the non-mcr-1 isolates produced the negative results. The sensitivity of mcr-1-MCDA-LFB assay was as little as 600 fg of plasmid DNA per reaction in pure culture, and approximately 4.5×103 CFU/mL (～4.5 CFU/reaction) in spiked fecal samples. Therefore, this technique established in the present study is suitable for the surveillance of mcr-1 gene in clinic and livestock industry.